PENINGKATAN KEMAMPUAN PEMASARAN DAN PEMBUKUAN SEDERHANA DI DESA INOVASI KELAUTAN DAN PERIKANAN - Hendra Poltak; Muhfizar Muhfizar; Jaulim Sirait; Ristiani; Ismail (Politeknik Negeri Sriwijaya, 2022)
Innovation village is a village that has the potential to be developed into an independent and empowered village. Problems in the village in the form of difficulties and marketing its business products and the need for simple bookkeeping understanding as the basis for its business continuity. Efforts to achieve the goal are carried out community service in accordance with mutual agreement. The activity was carried out using a face-to-face lecture method attended by 20 target partners. The results of the activity obtained an increase in understanding of marketing management by 60% and an increase in simple bookkeeping understanding by 45%.